Relationships between happiness and gender, age and marital status - Alarcón, Reynaldo (2001)
The present research examines the relationships between happiness and variables of gender, age and marital status as well as the degrees of happiness most frequently experienced by people. The sample was constituted by 163 males and females, between the ages of 20 and 60 years, single and married, and from middle class strata. They were administered the Scale of Satisfaction with Life, developed by Diener, with and added item to measure the degrees of happiness. There is no significan! statistically difference between genders; according to age the only significan contras! was between 30 and 50 years, with the notation that the highest means corresponded to ages 50 and 60 years old; married people were found to be happier than single ones. In general, the majority reported feeling happy, the other degrees contained very few frecuencies.